Methodology for the implementation of an economic and/or statistical design for x-bar charts with variable parameters (vp) (2014)
Recent advances in the design of control charts have focused on variable parameters charts (VP) in which parameters are modified according to the last sample value. These charts have proved more effective in detecting assignable causes but more complexes for implementation in organizations. Although, there is a lot literature regarding the economic and/or statistical design of a VP chart, few authors focus their efforts on making them accessible to companies. In this paper a new procedure is proposed to reduce the complexity and enhance the benefits of an economic and an economic-statistical design of X charts with variable parameters.